Generating essential user interface prototypes to validate requirements - massila, kamalrudin; john, grundy (2011)
Requirements need to be validated at an early stage of analysis to address inconsistency and incompleteness issues. Capturing requirements usually involves natural language analysis, which is often imprecise and error prone, or translation into formal models, which are difficult for non-technical stakeholders to understand and use. Users often best understand proposed software systems from the likely user interface they will present. To this end we describe novel automated tool support for capturing requirements as Essential Use Cases and translating these into “Essential User Interface” low-fidelity rapid prototypes. We describe our automated tool supporting requirements capture, lo-fi user interface prototype generation and consistency management.